Pengaruh Zakat dan Kesempatan Kerja terhadap Tingkat Kemiskinan di Aceh - Khairul Amri (AL-MUZARA'AH, 2019)
This study aims to analyze the effect of zakah revenues and job creation on poverty rates. Using a panel data set of 23 districts in Aceh for the period of 2011-2017, a fixed-effect method of the panel regression model and the Granger causality test was utilized to analyze the functional relationships between the three variables. The study found out that the zakah revenue and job creation have a negative and significant effect on poverty rates. However, the negative effect of job creation on poverty rates is greater than the negative effect of zakah revenues. The Granger causality test indicates that there is bidirectional causality between poverty rates and zakah revenues and between employment creation and poverty rates. Conversely, there is no causality between zakah revenues and job creations.